Triticum aestivum L. subsp. aestivum CWI 96214 ... - GLIS Of The ITPGRFA (Centro Internacional de Mejoramiento de Maíz y Trigo, 2017)
Plant Genetic Resource. Taxonomy: Triticum aestivum L. subsp. aestivum Common name(s): Wheat Other names: ARTICO Conserved by: Centro Internacional de Mejoramiento de Maíz y Trigo (CIMMYT), Mexico Local sample unique identifier: CWI 96214 Method of creation: Acquisition Date: 2014 Other identifiers: n/a,ARTICO, n/a,CWI96214, n/a,SCV-TA00081, n/a,CD66066, n/a,CID 125151 SID 0, n/a,GID 134774 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...